Basal cell carcinoma with compromised margins: retrospective study of management, evolution, and prognosis, - Maria Carolina Fidelis; Rafael Fantelli Stelini; Leonardo Piropo Staffa; Aparecida Machado de Moraes; Renata Ferreira Magalhães (Anais Brasileiros de Dermatologia, 2021)
Abstract Background: Non-melanoma skin cancer is the most common type of malignancy in the Western world, and surgical excision is the preferred approach. The approach adopted in the face of incomplete excisions of basal cell carcinoma is still controversial. Objectives: To compare the number of tumor recurrences after treatment for incompletely excised basal cell carcinoma. Methods: Selection and statistical analysis of medical records of patients who had compromised margins after excision of basal cell carcinoma in a tertiary hospital from 2008 to 2013. Results: A total of 120 medical records were analyzed; the mean age was 69.6 years, and 50% of the patients were female. The most prevalent histological type was nodular; the mean size was 1.1 cm, and the tumor location with the highest incidence was the nose. The lateral margin was the most frequently positive. Clinical follow-up was more widely adopted; only 40 patients underwent a second surgery. The total number of patients who had tumor recurrence was 34 (28.3%). Only the malar location significantly influenced the incidence of recurrence (p = 0.02). The mean follow-up time was 29.54 months, with no significant difference between the follow-ups, although 32.9% of the patients followed-up clinically showed recurrence, against only 20% of those who underwent a second surgery. Study limitations: Mean follow-up time of less than five years and sample size. Conclusions: The presence of compromised margins does not necessarily imply recurrence. Location, tumor size, histological subtype, previous epithelial tumors, and clinical conditions of the patient must be considered when choosing the best treatment option.